STUDENTS’ BEHAVIOUR ON USING CANVA APPLICATION FOR ENGLISH PROJECT - Hidayati, Reni (FKIP Unismuh Makassar, 2023)
Using technology is increasingly applied in teaching and learning in the 21st century. Technology has become an integral part of our lives and has greatly impacted various fields, including education. To adapt to increasingly massive learning technology, teachers need to be able to develop engaging and cutting-edge educational media for use in the classroom. Teachers today need to use more innovation to create engaging lessons. One of the popular platforms media in learning technology is the Canva application. This study aims to investigate students’ behaviour in the use of Canva applications for English projects. This research was conducted in January-March at SMPN 21 Semarang. Researchers used a descriptive qualitative method to describe qualitative data using questionnaires. The research sample was the 7th grade of SMPN 21 Semarang. The study results find that student behaviour using Canva application for English projects is a fun media for learning, enhancing students’ creativity, understanding, and motivation. But also, the Canva application has disadvantages such as the need for a stable connection and enough data for accessing the application.